Expanding the molecular-ruler process through vapor deposition of hexadecanethiol - Patron, Alexandra M.; Hooker, Timothy S.; Santavicca, Daniel F.; Causey, Corey P.; Mullen, Thomas J. (Beilstein Journal of Nanotechnology, 2017)
The development of methods to produce nanoscale features with tailored chemical functionalities is fundamental for applications such as nanoelectronics and sensor fabrication. The molecular-ruler process shows great utility for this purpose as it combines top-down lithography for the creation of complex architectures over large areas in conjunction with molecular self-assembly, which enables precise control over the physical and chemical properties of small local features. The molecular-ruler process, which most commonly uses mercaptoalkanoic acids and metal ions to generate metal-ligated multilayers, can be employed to produce registered nanogaps between metal features. Expansion of this methodology to include molecules with other chemical functionalities could greatly expand the overall versatility, and thus the utility, of this process. Herein, we explore the use of alkanethiol molecules as the terminating layer of metal-ligated multilayers. During this study, it was discovered that the solution deposition of alkanethiol molecules resulted in low overall surface coverage with features that varied in height. Because features with varied heights are not conducive to the production of uniform nanogaps via the molecular-ruler process, the vapor-phase deposition of alkanethiol molecules was explored. Unlike the solution-phase deposition, alkanethiol islands produced by vapor-phase deposition exhibited markedly higher surface coverages of uniform heights. To illustrate the applicability of this method, metal-ligated multilayers, both with and without an alkanethiol capping layer, were utilized to create nanogaps between Au features using the molecular-ruler process.
Keywords: hybrid nanolithography; metal-ligated multilayer; molecular ruler; self-assembled monolayers; vapor-phase deposition

(untitled) - Mullen, T. J.; Srinivasan, C.; Shuster, M. J.; Horn, M. W.; Andrews, A. M.; Weiss, P. S. (J. Nanopart. Res., 2008)

(untitled) - Saavedra, H. M.; Mullen, T. J.; Zhang, P.; Dewey, D. C.; Claridge, S. A.; Weiss, P. S. (Rep. Prog. Phys., 2010)

(untitled) - Smith, R. K.; Lewis, P. A.; Weiss, P. S. (Prog. Surf. Sci., 2004)

(untitled) - Whitesides, G. M.; Ostuni, E.; Takayama, S.; Jiang, X. Y.; Ingber, D. E. (Annu. Rev. Biomed. Eng., 2001)

(untitled) - Kasemo, B. (Surf. Sci., 2002)

(untitled) - Mantooth, B. A.; Weiss, P. S. (Proc. IEEE, 2003)

(untitled) - Tirrell, M.; Kokkoli, E.; Biesalski, M. (Surf. Sci., 2002)

(untitled) - Pathem, B. K.; Claridge, S. A.; Zheng, Y. B.; Weiss, P. S. (Annu. Rev. Phys. Chem., 2013)

(untitled) - Alivisatos, A. P.; Andrews, A. M.; Boyden, E. S.; Chun, M.; Church, G. M.; Deisseroth, K.; Donoghue, J. P.; Fraser, S. E.; Lippincott-Schwartz, J.; Looger, L. L.; Masmanidis, S.; McEuen, P. L.; et al. (ACS Nano, 2013)

(untitled) - Gates, B. D.; Xu, Q. B.; Stewart, M.; Ryan, D.; Willson, C. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Weiss, P. S. (Acc. Chem. Res., 2008)

(untitled) - Johnson, S.; Evans, D.; Davies, A. G.; Linfield, E. H.; Wälti, C. (Nanotechnology, 2009)

(untitled) - Xia, Y. N.; Rogers, J. A.; Paul, K. E.; Whitesides, G. M. (Chem. Rev., 1999)

(untitled) - Hatzor, A.; Weiss, P. S. (Science, 2001)

(untitled) - Anderson, M. E.; Smith, R. K.; Donhauser, Z. J.; Hatzor, A.; Lewis, P. A.; Tan, L. P.; Tanaka, H.; Horn, M. W.; Weiss, P. S. (J. Vac. Sci. Technol., B, 2002)

(untitled) - Anderson, M. E.; Srinivasan, C.; Hohman, J. N.; Carter, E. M.; Horn, M. W.; Weiss, P. S. (Adv. Mater., 2006)

(untitled) - Anderson, M. E.; Srinivasan, C.; Jayaraman, R.; Weiss, P. S.; Horn, M. W. (Microelectron. Eng., 2005)

(untitled) - Anderson, M. E.; Tan, L. P.; Tanaka, H.; Mihok, M.; Lee, H.; Horn, M. W.; Weiss, P. S. (J. Vac. Sci. Technol., B, 2003)

(untitled) - Srinivasan, C.; Anderson, M. E.; Carter, E. M.; Hohman, J. N.; Bharadwaja, S. S. N.; Trolier-McKinstry, S.; Weiss, P. S.; Horn, M. W. (J. Vac. Sci. Technol., B, 2006)

(untitled) - Srinivasan, C.; Hohman, J. N.; Anderson, M. E.; Weiss, P. S.; Horn, M. W. (J. Vac. Sci. Technol., B, 2007)

(untitled) - Srinivasan, C.; Hohman, J. N.; Anderson, M. E.; Weiss, P. S.; Horn, M. W. (Appl. Phys. Lett., 2008)

(untitled) - Tanaka, H.; Anderson, M. E.; Horn, M. W.; Weiss, P. S. (Jpn. J. Appl. Phys., Part 2, 2004)

(untitled) - McCarty, G. S. (Nano Lett., 2004)

(untitled) - Li, C. B.; Hasegawa, T.; Tanaka, H.; Miyazaki, H.; Odaka, S.; Tsukagoshi, K.; Aono, M. (Nanotechnology, 2010)

(untitled) - Anderson, M. E.; Mihok, M.; Tanaka, H.; Tan, L. P.; Horn, M. W.; McCarty, G. S.; Weiss, P. S. (Adv. Mater., 2006)

(untitled) - McCarty, G. S.; Moody, B.; Zachek, M. K. (J. Electroanal. Chem., 2010)

(untitled) - Daniel, T. A.; Uppili, S.; McCarty, G.; Allara, D. L. (Langmuir, 2007)

(untitled) - Benson, A. S.; Elinski, M. B.; Ohnsorg, M. L.; Beaudoin, C. K.; Alexander, K. A.; Peaslee, G. F.; DeYoung, P. A.; Anderson, M. E. (Thin Solid Films, 2015)

(untitled) - Johnson, S.; Chan, J.; Evans, D.; Davies, A. G.; Wälti, C. (Langmuir, 2011)

(untitled) - Evans, S. D.; Ulman, A.; Goppert-Berarducci, K. E.; Gerenser, L. J. (J. Am. Chem. Soc., 1991)

(untitled) - Freeman, T. L.; Evans, S. D.; Ulman, A. (Thin Solid Films, 1994)

(untitled) - Drexler, C. I.; Moore, K. B., III; Causey, C. P.; Mullen, T. J. (Langmuir, 2014)

(untitled) - Kim, Y. T.; McCarley, R. L.; Bard, A. J. (Langmuir, 1993)

(untitled) - Woodward, J. T.; Walker, M. L.; Meuse, C. W.; Vanderah, D. J.; Poirier, G. E.; Plant, A. L. (Langmuir, 2000)